Forest structure of Mediterranean yew (Taxus baccata L.) populations and neighbor effects on juvenile yew performance in the NE Iberian Peninsula - Casals, Pere; Camprodon, Jordi; Caritat, Antonia; Rios, Ana I.; Guixé, David; Garcia-Marti, Xavier; Martín-Alcón, Santiago; Coll, Lluis (Forest Systems, 2015)
Aim of study: In the Mediterranean region, yew (Taxus baccata L.) usually grows with other tree species in mixed forests. Yew recruitment and juvenile growth may depend on the structure of the forest and the net balance between competition for soil water and nutrients with neighbors and facilitation that these neighbors exert by protecting the plants from direct sun exposure. This study aims, at a regional scale, to analyze the structure of forests containing yew, and, on an individual level, to analyze the effect of the surrounding vegetation structure on the performance of yew juveniles.Area of study: The structural typologies of yew populations were defined based on field inventories conducted in 55 plots distributed in 14 localities in the North-Eastern (NE) Iberian Peninsula, covering a wide range of yew distribution in the area. In a second step, an analysis of neighboring species' effects on juveniles was conducted based on the data from 103 plots centered in yew juveniles in five localities.Main Results: A cluster analysis classified the inventoried stands into four forest structural types: two multi-stratified forests with scattered yew and two yew groves. Multiple regression modeling showed that the δ13C measured in last year's leaves positively relates to the basal area of conifer neighbors, but negatively with the cover of the yew crown by other trees.Research highlights: At a stand-level, the density of recruits and juveniles (625 ± 104 recruits ha-1, 259 ± 55 juveniles ha-1) in mixed forests was found to be higher than that on yew dominant stands (181 ± 88 recruits ha-1 and 57 ± 88 juveniles ha-1). At an individual-level, the water stress (estimated from leaf δ13C) of yew juveniles seems alleviated by the crown cover by neighbors while it increases with the basal area of conifers. Yew conservation should focus on selective felling for the reduction of basal area of neighbors surrounding the target tree, but avoid affecting the canopy cover to contribute to enhanced yew juvenile growth.Keywords: Biodiversity conservation; δ13C; forest management; plant-plant interaction; recruitment; Taxus baccata; water use efficiency.